PERKAWINAN ADAT MASYARAKAT NDESKATI DIKAITKAN DENGAN KOMPILASI HUKUM ISLAM - Sumiati, Syawaluddin, Syarifuddin Elhayat, (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
This study discusses the traditional marriage of the Ndeskati community associated with the Compilation of Islamic Law. There are two main issues that will be discussed in this study: first, how is the implementation of traditional marriages for the people of Ndeskati Village, Naman Teran District, Karo Regency, and secondly, how far is the influence of the Compilation of Islamic Law on the implementation of marriages in Ndeskati Village, Naman Teran District, Karo Regency. The purpose of this study was to find out how the implementation of traditional marriages for the people of Ndeskati Village, Naman Teran District, Karo Regency, and to determine the effect of the Compilation of Islamic Law on the implementation of marriages in Ndeskati Village, Naman Teran District, Karo Regency. In this study the authors used field research (Field Research) with a descriptive qualitative approach. The instruments used in this study were the researchers themselves using assistive devices in the form of pens, books, cameras, voice recorders and interviews. The data analysis technique used is a qualitative descriptive data analysis technique. The results of the study show that firstly the Ndeskati Village Community of Karo Regency views marriage as a very important thing so that a man and a woman can live together so that the resulting child has a legal status in the community; secondly, the Compilation of Islamic Law (Inpres No.l. / 1991), does not provide a detailed explanation of the technical implementation of marriage, so it is adat that can complete it so that Law No.1 of 1974 and RI Presidential Decree No.1 of 1991 have an influence on the implementation of customary marriages in the people of Ndeskati Village, Karo Regency, so that almost all of them synergize and implement the Compilation of Islamic Law in the case of indigenous peoples' marriages in Ndeskati Village. It turns out that the traditional marriage of the Ndeskati people does not violate the Compilation of Islamic Law.